ANALISIS PEMASARAN KARET DI DESA BAYAS JAYA KECAMATAN KEMPAS KABUPATEN INDRAGIRI HILIR - Ria ti (Menara Ilmu, 2017)
The purpose of this study are: analyze rubber marketing channel, marketing function, rubbermarkrting efficiency, rubber marketing margins, and to find out Share of Farmers. Result ofstudy is useful as an information and evaluation to farmers, rubber traders of channels,marketing functions and rubber marketing efficiency, and reference policies related to currymarketing.Data collected in this study are primary data and secondary data. Primary datawere obtained from interviews directly in the field. while secondary data obtained fromgovernment agencies that CPM. Data analysis used descriptive analysis. Based on theresearch results, there are two rubber marketing channels in the village of Bayas Jaya.Channel Marketing I: Marketing rubber from farmers to traders village level and then to thewholesalers to the factory. Marketing channel II: farmers sell to wholesalers to the factory.Marketing functions that occur at the village level traders is as a function of the exchange andthe large traders who do the marketing function is a function of exchange and physicalfunction. I channel marketing margin is smaller than the second channel marketing margin forthe marketing efficiency of both institutions are efficient. Part of the price received by farmersis the same for both marketing channels.Keywords: Marketing, Rubber, Farmers